Investigation of the fabrication process of metal 3D printed powder by molten alloy dispersion method using centrifugation and high-pressure gas - Nguyễn Tiến Mạnh; Đoàn Văn Phúc; Ninh Đức Hà; Lê Minh Trí; Trần Xuân Tiến (Journal of Military Science and Technology, 2024)
Atomization using centrifugation and high-pressure gas is considered to be a relatively new method of producing metal 3D printing powders. The metal powder made by this method is expected to obtain an adequate small-scaled size with the limitation of satellites stuck to the surface due to the reduction of the gas flow in the dispersion chamber. This work conducted experimental studies with aluminum alloy graded AlSi10Mg. The manufactured metal powder was tested for corresponding technical properties of metal 3D printing powder, such as chemical composition, particle size distribution, morphological structure, etc. The investigation results have determined the influence of geometrical and technological parameters of the atomization process, including liquid metal flow, liquid metal overheating, and some structural parameters of equipment on the quantity and quality of the product.